Spatial Relations in the Indonesian Locative Preposition of â€œDi Atasâ€: a Study of Cognitive Semantics - Joko Kusmanto; Sarmedi Agus Siregar; Mariahari Mariahati (Universitas Ahmad Dahlan, 2021)
This study examines the spatial relation of the preposition